MAX‐phase Derived Tin Diselenide for 2D/2D Heterostructures with Ultralow Surface/Interface Transport Barriers toward Li‐/Na‐ions Storage (Small Methods 9/2022). Issue 9 (19th September 2022) - Mei, Jun; Shang, Jing; Zhang, Chao; Qi, Dongchen; Kou, Liangzhi; Wijerathne, Binodhya; Hu, Chunfeng; Liao, Ting; MacLeod, Jennifer; Sun, Ziqi
Abstract : Ion Transport Barriers In article number 2200658, Mei, Sun, and co‐workers proposed a tin‐extracted synthetic strategy for producing tin diselenide by using MAX‐phase precursors. After coupled with graphene, the 2D heterostructure shows low surface/interface transport barriers in rechargeable Li‐/Na‐ion batteries.